2002
DOI: 10.1002/1522-2640(200205)74:5<649::aid-cite1111649>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative On-line-Konzentrationsmessung in Flüssig/Gas-Gemischen bei erhöhten Drücken und Temperaturen mit Raman-Spektroskopie

Abstract: P r o f. D r. -I n g . S. R i p p e r g e r 1 ) D r. -I n g . J. A l t m a n n 2 )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, they cannot answer the question if Raman spectr oscopy is applicable for investigations in the vicinity of the dew line. The closest resemblance to such studies can be found in the investigations of Stratmann and Schweiger [17,18]. They investigated fluid-phase equilibria of ethanol and carbon dioxide (CO 2 ) utilizing Raman spectroscopy.…”
Section: Literature Overview: Raman Spectroscopy For Gas Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…Thus, they cannot answer the question if Raman spectr oscopy is applicable for investigations in the vicinity of the dew line. The closest resemblance to such studies can be found in the investigations of Stratmann and Schweiger [17,18]. They investigated fluid-phase equilibria of ethanol and carbon dioxide (CO 2 ) utilizing Raman spectroscopy.…”
Section: Literature Overview: Raman Spectroscopy For Gas Analysismentioning
confidence: 96%
“…This includes measurements in polluted air [9], combustion gases [10][11][12], motor exhaust gases [13], fusion fuel gas processing [14] and vapor mixtures [15]. Binary mixtures have also been investigated to derive their composition and density from their spectra or to track fluid-phase equilibria [16][17][18]. More recently, investigations focused on the development of multicomponent gas analyzers, e.g., for natural gas and biogas, spatially resolved methods and solubility measurements in supercritical fluids [19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Literature Overview: Raman Spectroscopy For Gas Analysismentioning
confidence: 99%